Features of localization of wave energy at rough surfaces of piezodielectric waveguide - A. S. Avetisyan; Kamalyan, A. A.; Hunanyan, A. A. (National Academy of Sciences of Armenia)
Propagation of high-frequency electro-elastic normal wave signal in a composite waveguide is investigated. The composite waveguide consists of a base piezoelectric layer with rough surfaces, which respectively are filled with an ideal conductor and ideal dielectric. The problem is solved by the method of virtual cross sections and input of Magneto Elastic Layered Systems (MELS) hypotheses. The influence of surfaces roughness, as well as and the influence of surface smoothness (the effects of different physical and mechanical boundary conditions) on the process of propagation of high frequency electro-elastic normal wave signal is discussed. The behaviors of wave amplitude and frequency characteristics in the composite waveguide are numerically investigated at the propagation of normal wave signal. It is shown that if the surface roughness of the piezoelectric layer is not filled, only one shortwave mode occurs. The filling of the surface roughness with dielectric and conductor, leads to the appearance of up to four such wave modes, depending on the length of the wave signal. The dispersion dependencies for all possible characteristic modes of shear elastic waves are given. It is shown that on the propagation of slow waves, occurs frequency zone of silence at certain wave lengths. Исследуется распространение высокочастотного электроупругого волнового сигнала в композитном волноводе. Волновод состоит из базового пьезоэлектрического слоя с шероховатыми поверхностями, которые залиты соответственно идеальным проводником и идеальным диэлектриком. Решение проводится использованием виртуальных срезов и вводом гипотез MELS (hypothesis of Magneto Elastic Layered Systems). Обсуждаются как воздействие шероховатости поверхностей, так и эффект поверхностного сглаживания разными материалами (эффект разных физико-механических граничных условий) на процесс распространения высокочастотного электроупругого нормального сигнала. Численно исследованы амплитудное распределения и частотная характеристика волнового поля в композитном волноводе при распространении нормального волнового сигнала. Показано что, если поверхностные шероховатости не залиты, в волноводе возникает только одна коротковолновая мода. Заливка поверхностных негладкостей приводит к появлению до четырёх таких волновых мод в зависимости от длины волнового сигнала. Приведены дисперсионные зависимости для всех возможных характерных мод волны упругого сдвига. Оказывается, что в случае распространения медленных волн, возникает зона частотного умолчания для волн определённых длин. Դիտարկվում է բարձր հաճախականային էլեկտրա-առաձգական ալիքային ազդանշանի տարածումը բաղադրյալ ալիքատարում: Ալիքատարը բաղկացած է անհարթ մակերևույթներով հիմնական պյեզոէլեկտրիկ շերտից, որը սոսնձված է համապատասխանաբար իդեալական հաղորդիչով և իդեալական դիէլեկտրիկով: Խնդիրը լուծվում է վիրտուլ հատումների մեթոդով և MELS վարկածների ներմուծումով: Քննարկվում է ինչպես մակերևույթի անհարթության ազդեցությունը, այնպես էլ տարբեր նյութերով մակերևույթի մեղմացման ազդեցությունը (տարբեր ֆիզիկա-մեխանիկական եզրային պայմանների ազդեցությունները) բարձր հաճախականային էլէկտրա-առաձգական նորմալ ալիքի տարածման ժամանակ: Կատարվել են ամպլիտուդայի բաշխման և ալիքային դաշտի հաճախականային բնութագրերի թվային հետազոտություններ առաձգական ալիքատարում: Ցույց է տրված, որ եթե մակերևույթային անհարթությունները սոսնձված չեն, ալիքատարում առաջանում է միայն մեկ կարճ հաճախականային ձև: Մակերևույթային անհարթությունները սոսնձումը բերում է մինչև չորս, կախված ալիքային ազդանշանի երկարությունից, այդպիսի ալիքային ձևերի առաջացման: Բերված է դիսպերսիոն կախվածությունը առաձգական սահքի ալիքային ձևերի բոլոր բնութագրիչներից: Ցույց է տրված, որ դանդաղ ալիքների տարածման դեպքում, որոշակի երկարության ալիքների համար, առաջանում է հաճախականության լռության գոտիներ:
Keywords: Mechanics of deformable solids; Coupling of solid mechanics with other effects; Waves